The Chromone Alkaloid, Rohitukine, Affords Anti-Cancer Activity via Modulating Apoptosis Pathways in A549 Cell Line and Yeast Mitogen Activated Protein Kinase (MAPK) Pathway - Safia; Kamil, Mohd; Jadiya, Pooja; Sheikh, Saba; Haque, Ejazul; Nazir, Aamir; Lakshmi, Vijai; Mir, Snober S. (PLOS ONE, 2015)
The field of cancer research and treatment has made significant progress, yet we are far from having completely safe, efficient and specific therapies that target cancer cells and spare the healthy tissues. Natural compounds may reduce the problems related to cancer treatment. Currently, many plant products are being used to treat cancer. In this study, Rohitukine, a natural occurring chromone alkaloid extracted from Dysoxylum binectariferum, was investigated for cytotoxic properties against budding yeast as well as against lung cancer (A549) cells. We endeavored to specifically study Rohitukine in S. cerevisiae in the context of MAPK pathways as yeast probably represents the experimental model where the organization and regulation of MAPK pathways are best understood. MAPK are evolutionarily conserved protein kinases that transfer extracellular signals to the machinery controlling essential cellular processes like growth, migration, differentiation, cell division and apoptosis. We aimed at carrying out hypothesis driven studies towards targeting the important network of cellular communication, a critical process that gets awry in cancer. Employing mutant strains of genetic model system Saccharomyces cerevisiae. S. cerevisiae encodes five MAPKs involved in control of distinct cellular responses such as growth, differentiation, migration and apoptosis. Our study involves gene knockouts of Slt2 and Hog1 which are functional homologs of human ERK5 and mammalian p38 MAPK, respectively. We performed cytotoxicity assay to evaluate the effect of Rohitukine on cell viability and also determined the effects of drug on generation of reactive oxygen species, induction of apoptosis and expression of Slt2 and Hog1 gene at mRNA level in the presence of drug. The results of this study show a differential effect in the activity of drug between the WT, Slt2 and Hog1 gene deletion strain indicating involvement of MAPK pathway. Further, we investigated Rohitukine induced cytotoxic effects in lung cancer cells and stimulated the productions of ROS after exposure for 24 hrs. Results from western blotting suggest that Rohitukine triggered apoptosis in A549 cell line through upregulation of p53, caspase9 and down regulation of Bcl-2 protein. The scope of this study is to understand the mechanism of anticancer activity of Rohitukine to increase the repertoire of anticancer drugs, so that problem created by emergence of resistance towards standard anticancer compounds can be alleviated.